ANALISIS KEBUTUHAN LUASAN AREA HIJAU BERDASARKAN DAYA SERAP CO2 DI KOTA MALANG, JAWA TIMUR - RM Mulyadin; R.Esa Pangersa Gusti (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
High urban activities have an impact on the environmental quality degradation due to the increase of carbondioxide (CO2) gas pollution. An efforts to reduce concentration of CO2 in the urban air is by developing green area or better known as green open space (RTH). One of RTHwhich appropriate with urban area is urban forest. This study aims to determine suitability of green area with total emission generated in Malang city. Eleven-point of urban forest has been analyzed. Total emission measures from four sources, such as emission from fuel, residents, livestocks and rice field. The results showed that the existing green areas have not been able to absorb the total emissions. The addition of 3,373.022 ha green area is required to absorb total emission in the city.